4(2-x)+15=3(x=3)

Simple and best practice solution for 4(2-x)+15=3(x=3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2-x)+15=3(x=3) equation:



4(2-x)+15=3(x=3)
We move all terms to the left:
4(2-x)+15-(3(x)=0
We add all the numbers together, and all the variables
4(-1x+2)-(3x+15=0
We multiply parentheses
-4x-(3x+15+8=0

See similar equations:

| 4^x=272 | | 3n-14=-2 | | 5/7z-3/7z+9/7z=z/7+4 | | 35x-42=8x | | 4^x+2+4^x=272 | | 5x+3x=8-243 | | 4,17z=-2+17z | | 417z=-2+17z | | y=3+5(10) | | 4d=-1+3d | | 0.2k-0.1=0.94 | | y=3+5(9) | | 176=4m | | 2z+7=z+6 | | n+4/4n-8=5/12 | | y=3+5(5) | | 2x+4×x=48 | | -6y-48=4y | | y=3+5(3) | | -7t=-7-6t | | 9x-3x-4=6x-2 | | (2x-15)=(x+17) | | |-n+5|=11 | | 13y-45=8y+20 | | (10^5)x7=56 | | 4p−p+2p=15 | | 3x+45=2x+90 | | 85+2x-17=185 | | 4.6x-1.1=8.1 | | |−n+5|=11 | | 13k−12k+3k+3k=14 | | F(x)=4x^2+7x+11 |

Equations solver categories